إنهاء عقد الوكالة التجارية: دراسة خاصة لوكالة العقود في القانون الكويتي: دراسة مقارنة - المري، عايض راشد (جامعة المنصورة - كلية الحقوق, 2021)
تناولنا في هذه الدراسة إنهاء عقد وكالة العقود، وآثار ذلك الإنهاء على أطراف العقد في دولة الكويت، من حيث الأسباب المشروعة لانتهاء عقد وكالة العقود. فتناولنا الإنهاء التعسفي لعقد وكالة العقود، كما في حالة عزل الوكيل للموكل، وموقف المشرع في هذه الحالة، خاصة وأن عقد وكالة العقود من عقود المصلحة المشتركة، فالمشرع الكويتي نص على عدم جواز إنهاء الوكالة دون خطأ من الوكيل، وإلا كان ملزما بتعويضه عن الضرر الذي لحقه من جراء عزله، وأبطل المشرع كل اتفاق يخالف ذلك؛ لتعلق ذلك بالنظام العام. كذلك في حال ما إذا كان هناك تواطؤ بين الموكل وشخص آخر) وكيل جديد (على استبدال الوكيل القديم، فإن المشرع الكويتي جعل هذا الوكيل الجديد مسئولا بالتضامن مع الموكل عن الوفاء بالتعويضات المحكوم بها للوكيل السابق. وفي مبحث مستقل، تناولنا التعويض المستحق نتيجة تعسف الموكل في إنهاء عقد وكالة العقود، فتعرفنا على عناصره المتمثلة في: التعويض عن عنصر العملاء، وجبر الضرر الذي لحق الوكيل جراء أنهاء عقد وكالة العقود. وحرصا من المشرع الكويتي على تقصير أمد النزاع بين طرفي العقد، فقد نص على أن دعوى التعويض تسقط بمضي تسعين يوما من وقت انتهاء العقد، وتسقط جميع الدعاوى الأخرى الناشئة عن عقد وكالة العقود بانقضاء ثلاث سنوات على انتهاء العلاقة التعاقدية كما في حالة إنهاء العقد خلال سريانه، كما جعل الاختصاص القضائي لنظر منازعات عقد وكالة العقود للمحكمة التي يقع في دائرتها محل تنفيذ العقد، وذلك استثناء من قواعد الاختصاص التي نص عليها قانون المرافعات الكويتي؛ تيسيرا على وكلاء العقود في المطالبة بحقوقهم. وفي المطلب الأخير، تناولنا التحكيم كوسيلة لتسوية المنازعات في عقد وكالة العقود، فمعظم عقود وكالة العقود التي تبرمها الشركات الأجنبية تتضمن شرط التحكيم في حال نشوب نزاع متعلق بعقد الوكالة، وتتم الإحالة إلى مراكز التحكيم الأجنبية خارج دولة الكويت، لثقتهم في تلك المراكز ومعرفتهم الجيدة بإجراءاتها، وبحثنا مدى أحقية تلك الشركات في تضمين ذلك الشرط في عقودهم. In this study, we examined the expiration of the contract agency contract, and the effects of that termination on the parties to the contract in the State of Kuwait, in terms of legitimate reasons for the expiration of the contract agency contract. The agency of contracts ends with the completion of the work entrusted to it, or the expiry of the term assigned to the agency, or the death of the client or the agent, or the loss of one of their eligibility due to a symptom of eligibility, or because of bankruptcy, then we dealt with the case of force majeure and the foreign cause, and the extent of the agent's entitlement to compensation for the agency’s termination in the event of a force majeure. Then, we dealt with the arbitrary termination of the contract agency contract, as in the case of the removal of the client by the agent, and the position of the legislator in this case, especially since the contract agency contract is a contract of common interest. Otherwise, he shall be obligated to compensate him for the damage he sustained as a result of his dismissal, and the legislator shall void any agreement to the contrary; as it is related to public order. Likewise, if there is collusion between the client and another person (a new agent) over the replacement of the old agent, the Kuwaiti legislator has made this new agent responsible, in solidarity with the client, for fulfilling the damages awarded to the previous agent. In a separate chapter, we dealt with the compensation due to the arbitrariness of the agent to terminate the contract agency contract. We learned about its elements: compensation for the customer’s element, and reparation for the damage caused to the client by terminating the contract agency contract. The Kuwaiti legislator is keen to shorten the duration of the dispute between the two parties of the contract, it stipulated that the claim for compensation will be dropped after the lapse of ninety days from the time of the end of the contract, and all other cases arising from the contract agency contract will lapse after three years after the end of the contractual relationship, and also made the jurisdiction to consider disputes of the contract agency contract of the court in whose jurisdiction the execution of the contract is located, in exception of the rules of jurisdiction stipulated in the Kuwaiti Procedure Law; In order to facilitate contract agents in claiming their rights, and in the last topic, we addressed arbitration as a method of settling disputes in a contract agency contract.
Keywords: العقود التجارية -- وكالة العقود -- دعاوي التعويض -- تسوية المنازعات -- القانون الكويتي